2021
DOI: 10.1002/dc.24903
|View full text |Cite
|
Sign up to set email alerts
|

Application of immunocytochemical and molecular analysis of six genes in liquid‐based endometrial cytology

Abstract: Background: The Yokohama System of Endometrial Cytology has been used for reporting endometrial cytology, which includes gray zone category, atypical endometrial cells (ATEC), subdivided into ATEC-US and ATEC-AE. ATEC-US has been reported to be correlated with malignancy in nearly 10% of the cases. For accurate diagnosis, application of ancillary techniques on endometrial cytology was investigated.Methods: Thirty-seven liquid based cytological specimens (SurePath™) with diagnosis of ATEC or malignant which hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In our previous study, immunocytochemistry and driver gene mutation of six genes were studied by using LBC cytology sample. 33 Akahane et al also used LBC samples and made next-generation sequencing analysis giving compatible results with those of formalin-fixed paraffin-embedded tissue. 34,35 Their study extends the possibility of utilizing the LBC materials to multiple gene analysis by next generation sequencer.…”
Section: Diagnostic Classification Of Endometrial Cytologymentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, immunocytochemistry and driver gene mutation of six genes were studied by using LBC cytology sample. 33 Akahane et al also used LBC samples and made next-generation sequencing analysis giving compatible results with those of formalin-fixed paraffin-embedded tissue. 34,35 Their study extends the possibility of utilizing the LBC materials to multiple gene analysis by next generation sequencer.…”
Section: Diagnostic Classification Of Endometrial Cytologymentioning
confidence: 99%
“…Recently, molecular analysis was employed on endometrial cytology. In our previous study, immunocytochemistry and driver gene mutation of six genes were studied by using LBC cytology sample 33 . Akahane et al also used LBC samples and made next‐generation sequencing analysis giving compatible results with those of formalin‐fixed paraffin‐embedded tissue 34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…The standardized diagnostic algorithm using cytomorphological assessment of LBC samples, also known as the Osaki Study Group method, has recently been demonstrated to be reliable and reproducible [ 11 ]. The application of immunocytochemistry and molecular technology techniques for endometrial cytology sample processing has been studied to improve the diagnostic accuracy of endometrial cytology [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Endometrial biopsy mainly includes D&C, hysteroscopy and hysterectomy.…”
Section: Introductionmentioning
confidence: 99%